Polishing pad, polishing device, and manufacturing method for polishing pad
By modifying hollow particles in the polishing pad with reactive functional groups to enhance adhesion to polyurethane resin, the issue of scratches caused by non-expandable hollow particles in conventional polishing pads is addressed, resulting in improved polishing performance.
Patent Information
- Application Number
- JP2023166568
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
AI Technical Summary
Conventional polishing pads using non-expandable hollow particles with small particle sizes (1 μm to 20 μm) experience decreased adhesion to polyurethane resin, leading to scratches on polished objects during chemical mechanical polishing (CMP) processes.
A polishing pad with a polishing layer containing a polyurethane resin and hollow particles, where the hollow particles have a particle size of 1 μm or more and 20 μm or less, and are modified with reactive functional groups that react with an isocyanate-group-terminated urethane prepolymer and a curing agent, enhancing adhesion and reducing scratches.
The proposed solution improves the adhesion of hollow particles to polyurethane resin, reducing the occurrence of scratches on polished objects and enhancing the overall polishing performance.
Smart Images

Figure 2025056987000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad, a polishing apparatus, and a method for manufacturing a polishing pad. [Background technology]
[0002] Conventionally, chemical mechanical polishing (CMP) using a slurry and a polishing pad has been used to polish objects such as semiconductor wafers because extremely precise flatness is required for such objects. CMP is a method in which a slurry is supplied to the polishing surface of a rotating polishing pad while pressing the object to be polished, such as a semiconductor wafer, against the polishing pad and rotating the pad to polish the surface of the object.
[0003] Currently, it is known that hollow particles are dispersed in the polishing layer constituting the polishing pad (see, for example, Patent Document 1). In the polishing layer containing such hollow particles, the hollow particles are located on the surface of the polishing layer and have open holes, so that the slurry can be held inside the hollow particles, and therefore a large amount of slurry can be held on the surface of the polishing layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-182314 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, if the hollow particles are non-expandable and the diameter of the hollow particles (D 50) is small, 1 μm or more and 20 μm or less, the adhesion between the hollow particles and the polyurethane resin decreases, and scratches may occur on the object to be polished. Patent Document 1 describes that the filler has a functional group such as -NH2, but does not pay any attention to the fact that when non-expanding hollow particles having a size of 1 μm or more and 20 μm or less are used, the adhesion between the hollow particles and the polyurethane resin decreases, and scratches may occur on the object to be polished.
[0006] The present invention has been made to solve the above problems. 50 The present invention aims to provide a polishing pad, a polishing apparatus, and a method for manufacturing a polishing pad that can improve the adhesion of hollow particles to a polyurethane resin in a polishing layer using hollow particles having a diameter of 1 μm or more and 20 μm or less, thereby reducing the occurrence of scratches on an object to be polished. [Means for solving the problem]
[0007] [1] A polishing pad having a polishing layer containing a polyurethane resin and hollow particles dispersed in the polyurethane resin, the polishing layer being a cured product of a curable resin composition containing an isocyanate group-terminated urethane prepolymer, a curing agent, and non-expandable hollow particles, the particle diameter (D 50 ) is 1 μm or more and 20 μm or less, and the hollow particles have an outer shell and a reactive functional group that is modified on the surface of the outer shell and reacts with at least one of the isocyanate group-terminated urethane prepolymer and a curing agent.
[0008] [2] The polishing pad according to [1] above, wherein the reactive functional group is a functional group that reacts with the isocyanate group-terminated urethane prepolymer.
[0009] [3] The polishing pad according to [1] or [2] above, wherein the reactive functional group is a hydroxyl group.
[0010] [4] The polishing pad according to any one of [1] to [3] above, wherein the surface of the polishing layer has pores, and the average opening diameter of the pores is 1 μm or more and 20 μm or less.
[0011] [5] A polishing apparatus comprising the polishing pad described in any one of [1] to [4] above.
[0012] [6] A method for producing a polishing pad having a polishing layer containing a polyurethane resin and hollow particles dispersed in the polyurethane resin, comprising the steps of: curing a curable resin composition containing an isocyanate group-terminated urethane prepolymer, a curing agent, and non-expandable hollow particles to obtain a block containing the urethane resin and hollow particles; and slicing the block to form a polishing layer, wherein the diameter (D 50 ) is 1 μm or more and 20 μm or less, and the hollow particles have an outer shell and a reactive functional group that is modified on the surface of the outer shell and reacts with at least one of the isocyanate group-terminated urethane prepolymer and a curing agent.
[0013] [7] The method for producing a polishing pad described in [6] above, wherein the reactive functional group is a functional group that reacts with the isocyanate group-terminated urethane prepolymer.
[0014] [8] The method for producing a polishing pad described in [6] or [7] above, wherein the reactive functional group is a hydroxyl group.
[0015] [9] A method for producing a polishing pad according to any one of [6] to [8] above, wherein the surface of the polishing layer has holes, and the average opening diameter of the holes is 1 μm or more and 20 μm or less. Effect of the Invention
[0016] According to the present invention, the non-swelling and particle size (D 50The present invention provides a polishing pad, a polishing apparatus, and a method for manufacturing a polishing pad that can improve the adhesion of hollow particles to a polyurethane resin in a polishing layer using hollow particles having a diameter of 1 μm or more and 20 μm or less, thereby reducing the occurrence of scratches on an object to be polished. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic diagram of a polishing pad according to an embodiment. [Diagram 2] FIG. 2 is an enlarged view of a portion of FIG. [Diagram 3] FIG. 3 is a schematic diagram of a polishing apparatus including a polishing pad according to an embodiment. [Figure 4] FIG. 4 is an SEM image of the surface of the polishing layer of the polishing pad according to Example 1 at a magnification of 5000 times. [Diagram 5] FIG. 5 is an SEM image of the surface of the polishing layer of the polishing pad of Example 2 at a magnification of 5000 times. [Figure 6] FIG. 6 is an SEM image at a magnification of 5000 times of the surface of the polishing layer of the polishing pad according to Comparative Example 1. [Figure 7] FIG. 7 is an SEM image at 1000 times magnification of the surface of the polishing layer of the polishing pad in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] A polishing pad and a polishing apparatus according to an embodiment of the present invention will be described below. Fig. 1 is a schematic diagram of the polishing pad according to this embodiment, Fig. 2 is an enlarged view of a part of Fig. 1, and Fig. 3 is a schematic diagram of the polishing apparatus including the polishing pad according to this embodiment.
[0019] <<<Polishing pads>>> 1, polishing pad 10 is, for example, disc-shaped and includes polishing layer 11, cushion layer 12, and adhesive layer 13 for adhering polishing layer 11 and cushion layer 12. Polishing pad 10 includes cushion layer 12 and adhesive layer 13, but it is sufficient to include polishing layer 11, and it is not necessary to include cushion layer 12 and adhesive layer 13. Surface 10A of polishing pad 10 is surface 11A of polishing layer 11.
[0020] <<Polishing layer>> 2, the polishing layer 11 contains urethane resin 11B and hollow particles 11C dispersed in the urethane resin 11B. The thickness of the polishing layer 11 can be about 1 to 5 mm.
[0021] The polishing layer 11 has holes on the surface 11A of the polishing layer 11. The average opening diameter of the holes is preferably 1 μm or more and 20 μm or less. If the average opening diameter of the holes is 1 μm or more, a large amount of slurry can be held near the surface 11A of the polishing layer 11 when the polishing object is polished. Furthermore, when the polishing object is polished, the polishing pad is scraped and polishing debris is generated, but if the average opening diameter is 20 μm or less, the polishing debris does not accumulate in the holes of the polishing layer 11, and the occurrence of scratches can be further reduced. The lower limit of the average opening diameter of the holes of the polishing layer 11 is more preferably 2 μm or more, 3 μm or more, or 4 μm or more, and the upper limit is more preferably 18 μm or less, 15 μm or less, or 10 μm or less. The average opening diameter can be measured by a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation).
[0022] The arithmetic mean height (Sa) of the surface 11A of the polishing layer 11 is preferably 2.0 μm or less. If the arithmetic mean height (Sa) is 2.0 μm or less, the contact pressure with the workpiece can be made uniform during polishing of the workpiece, so that the occurrence of scratches can be further reduced. The lower limit of the arithmetic mean height (Sa) may be 0 μm or more, and the upper limit is more preferably 1.8 μm or less, 1.5 μm or less, or 1.0 μm or less. The arithmetic mean height (Sa) is defined in ISO 25178. The arithmetic mean height (Sa) can be measured by a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation).
[0023] The density of the polishing layer 11 is not particularly limited, but is preferably 0.60 g / cm 3 More than 1.25g / cm 3 If the density is within the above range, the occurrence of scratches due to polishing by-products (polishing debris) can be reduced. The lower limit of the density of the polishing layer 11 is 0.65 g / cm 3 or more than 0.70g / cm 3 More preferably, the upper limit is 1.15 g / cm 3 or less than 1.10g / cm 3 The following is more preferable: The density of the polishing layer 11 can be measured according to the procedures and conditions described in the section <Measurement of Density of Polishing Layer> in the Examples below.
[0024] The Shore D hardness of the polishing layer 11 is not particularly limited, but is preferably 35 or more and 75 or less. If the Shore D hardness is 35 or more, minor irregularities can be flattened, and if the Shore D hardness is 75 or less, the occurrence of scratches on the polished object can be reduced. The lower limit of the Shore D hardness of the polishing layer 11 is more preferably 40 or more, or 45 or more, and the upper limit is more preferably 70 or less, or 65 or less. The Shore D hardness of the polishing layer 11 can be measured based on the procedure and conditions described in the <Shore D hardness measurement of the polishing layer> section of the Examples described later.
[0025] The polishing layer 11 is a cured product of a curable resin composition containing an isocyanate group-terminated urethane prepolymer, a curing agent, and hollow particles 11C.
[0026] <Isocyanate-terminated urethane prepolymer> The isocyanate-terminated urethane prepolymer is a compound obtained by reacting a polyisocyanate compound with a polyol compound under commonly used conditions, and contains a urethane bond and an isocyanate group in the molecule. In addition, other components may be contained in the isocyanate-terminated prepolymer within the range that does not impair the effects of the present invention.
[0027] The isocyanate-terminated prepolymer may be a commercially available product, or may be a product synthesized by reacting a polyisocyanate compound with a polyol compound. There is no particular limitation on the reaction, and the addition polymerization reaction may be carried out using a method and conditions known in the production of polyurethane resins. For example, the prepolymer may be produced by adding a polyisocyanate compound heated to 50°C to a polyol compound heated to 40°C while stirring in a nitrogen atmosphere, and then heating the polyol compound to 80°C after 30 minutes and reacting at 80°C for 60 minutes.
[0028] The isocyanate-terminated prepolymer preferably has an NCO equivalent (g / eq) of about 300 to 700. The NCO equivalent (g / eq) being within the above-mentioned range allows the polishing layer 11 to exhibit appropriate hardness and obtain the desired polishing performance. Therefore, when the isocyanate-terminated prepolymer is a commercially available product, it is preferable that the NCO equivalent (g / eq) satisfies the above-mentioned range, and when it is produced by synthesis, it is preferable to use the following raw materials in an appropriate ratio to obtain the NCO equivalent (g / eq) within the above-mentioned range. The lower limit of the NCO equivalent (g / eq) of the isocyanate-terminated prepolymer may be 350 or more, 400 or more, or 450 or more, and the upper limit is more preferably 680 or less, or 650 or less. The NCO equivalent (g / eq) is calculated by (parts by mass of polyisocyanate compound + part by mass of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × parts by mass of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × parts by mass of polyol compound / molecular weight of polyol compound)], and is a value indicating the molecular weight of prepolymer per NCO group.
[0029] (Polyisocyanate compounds) In this specification, the term "polyisocyanate compound" refers to a compound having two or more isocyanate groups in the molecule. The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule. For example, diisocyanate compounds having two isocyanate groups in the molecule include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyl ... Examples of the polyisocyanate include diphenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, ethylidine diisothiocyanate, etc. These polyisocyanate compounds may be used alone or in combination of a plurality of polyisocyanate compounds.
[0030] The polyisocyanate compound preferably contains 2,4-TDI and / or 2,6-TDI.
[0031] (Polyol Compound) In this specification, the polyol compound means a compound having two or more hydroxyl groups (OH) in the molecule. Examples of the polyol compound used in the synthesis of the urethane bond-containing polyisocyanate compound as a prepolymer include polyether polyol and polyester polyol.
[0032] Examples of polyether polyols include diol compounds, triol compounds, and the like, such as ethylene glycol, diethylene glycol (DEG), and butylene glycol; poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG), polypropylene glycol (PPG), and polyether polycarbonate diol (PEPCD).
[0033] The polyester polyol is, for example, a reaction product of a dicarboxylic acid component and a diol component, and is a type of high molecular weight polyol. The dicarboxylic acid component contained in the polyester polyol is not particularly limited, but includes aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, decanedioic acid, and dodecanedioic acid, unsaturated bond-containing dicarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid, aromatic dicarboxylic acids such as orthophthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, diphenic acid, and anhydrides thereof, and the like, or a combination of two or more of them. Among these dicarboxylic acid components, adipic acid is preferred.
[0034] The diol component contained in the polyester polyol is not particularly limited, but examples thereof include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, etc., which may be used alone or in combination. Among these diol components, 1,4-butanediol is preferred.
[0035] <Hardening agent> The curing agent is not particularly limited, but may be, for example, a polyamine. The curing agent may be used alone or in combination of two or more kinds.
[0036] The polyamine is not particularly limited, but examples thereof include aliphatic polyamines such as ethylenediamine, propylenediamine, and hexamethylenediamine; alicyclic polyamines such as isophoronediamine and dicyclohexylmethane-4,4'-diamine; and aromatic polyamines such as 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. In addition, trifunctional triamine compounds and polyamine compounds having 4 or more functional groups can also be used. Among these, aromatic polyamines are preferred, and it is more preferred to use 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA).
[0037] <Hollow particles> The hollow particles 11C are particles having a cavity inside. The shape of the hollow particles 11C is not particularly limited, but may be, for example, spherical or approximately spherical.
[0038] The hollow particles 11C are non-expandable, and the particle diameter (D 50 ) is 1 μm or more and 20 μm or less. The particle diameter (D 50 If the diameter (D) of the hollow particles 11C is 1 μm or more, a large amount of slurry can be held near the surface of the polishing layer 11 during polishing of the workpiece. 50 If the diameter (D) of the hollow particles 11C is 20 μm or less, polishing waste will not accumulate in the holes of the polishing layer 11, and the occurrence of scratches can be further reduced. 50 The lower limit of the particle diameter (D) of the hollow particles may be 2 μm or more, 3 μm or more, or 4 μm or more, and the upper limit of the particle diameter (D) of the hollow particles may be 18 μm or less, 15 μm or less, or 10 μm or less. 50) is also called the median diameter, and refers to the particle diameter at which the hollow particles are integrated from the smallest side to reach 50% volume in the cumulative particle size distribution obtained by measuring on a volume basis. 50 ) can be measured using a laser diffraction particle size distribution measuring device (for example, product name "Mastersizer 2000" manufactured by Spectris Co., Ltd.).
[0039] The hollow particle 11C has an outer shell 11C1 and a reactive functional group modified on the surface of the outer shell 11C1, which reacts with at least one of an isocyanate-terminated urethane prepolymer and a curing agent. The reactive functional group is not particularly limited as long as it is a functional group that reacts with at least one of an isocyanate-terminated urethane prepolymer and a curing agent, but a hydroxyl group is preferred. If the reactive functional group is a hydroxyl group, it can react with the isocyanate group of the isocyanate-terminated urethane prepolymer.
[0040] The reactive functional group can be introduced by performing a surface modification treatment on the surface of the outer shell 11C1. The method of the surface modification treatment is not particularly limited, but includes the addition of a silane coupling agent, plasma treatment, etc. Note that if the material of the outer shell 11C1 originally has a reactive functional group, the surface modification treatment does not need to be performed.
[0041] When the surface modification treatment is performed using a silane coupling agent, the treatment can be performed by a known method. For example, the surface modification treatment can be performed by adding a predetermined amount of a silane coupling agent to the hollow particles before surface modification, and then performing an acid treatment, an alkali treatment, a heat treatment, or the like as necessary.
[0042] When the surface modification treatment is performed using plasma, the treatment can be performed by a known method. For example, the surface modification treatment can be performed by irradiating the hollow particles before surface modification with plasma under vacuum or under a non-polymerizable gas atmosphere.
[0043] As the non-polymerizable gas used in the plasma treatment, for example, O2 or H2O can be used. By using a mixed gas of O2 gas and H2O gas, or O2 gas, the surface of the outer shell 11C1 can be modified with hydroxyl groups or carboxyl groups. The functional groups modified on the surface of the outer shell 11C1 may be of only one type, or may be of two or more types.
[0044] The material of the outer shell 11C1 of the hollow particle 11C is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polyvinylpyrrolidone-based polymers, poly(meth)acrylic acid-based polymers, polystyrene-based polymers, polyacrylamide-based polymers, polyethylene glycol-based polymers, polyhydroxyether acrylate-based polymers, maleic acid copolymer-based polymers, polyethylene oxide-based polymers, polyurethane-based polymers, acrylonitrile-based polymers, polyvinylidene chloride-acrylonitrile copolymer-based polymers, etc. Among these, poly(meth)acrylic acid-based polymers, polystyrene-based polymers, or acrylonitrile-based polymers are preferable from the viewpoint of obtaining the desired polishing performance.
[0045] The content of hollow particles 11C in polishing layer 11 is preferably 0.1% by mass or more and 30% by mass or less. If the content of hollow particles 11C is 0.1% by mass or more, a large amount of slurry can be held near the surface of polishing layer 11 during polishing of the workpiece, and if the content is 30% by mass or less, hollow particles 11C are uniformly dispersed without agglomeration, so that adhesion to urethane resin 11B is improved. The lower limit of the content is more preferably 0.5% by mass or more, 2.0% by mass or more, or 4.0% by mass or more, and the upper limit is more preferably 25% by mass or less, 20% by mass or less, or 15% by mass or less.
[0046] The polishing pad 10 is used to polish an object to be polished. The object to be polished is not particularly limited, but examples thereof include optical materials, semiconductor wafers, and glass substrates for hard disks.
[0047] <<Polishing pad manufacturing method>> Such a polishing pad 10 can be manufactured, for example, as follows: First, an isocyanate-terminated urethane prepolymer, a curing agent, and hollow particles are prepared.
[0048] Next, the isocyanate-terminated urethane prepolymer and the hollow particles are mixed and maintained at a temperature of 50° C. to 80° C. Meanwhile, the curing agent is maintained at about 120° C. The hollow particles may be added to the curing agent side.
[0049] Then, the isocyanate-terminated prepolymer and hollow particles are mixed with a curing agent to obtain a curable composition for the polishing layer. The curable composition for the polishing layer is then fed into a mold and heated at a temperature in the range of 75° C. to 140° C. to cure the curable composition for the polishing layer. This produces a block containing a urethane resin and hollow particles, which is a cured product of the curable composition for the polishing layer.
[0050] The hardened block is removed from the mold and sliced to a specified thickness to obtain the polishing layer. After grooves are formed on the surface of the polishing layer, it is bonded to the cushion layer via an adhesive layer. Finally, it is cut into a disk shape. This produces the polishing pad 10.
[0051] The reason why scratches are likely to occur when non-expanding hollow particles with small particle diameter are used is considered to be as follows. First, when using expandable hollow particles that contain organic solvents such as low boiling point hydrocarbons inside the shell and expand when heated, the hollow particles solidify while pushing against the polyurethane resin in the process of expanding when heated, so the adhesion between the polyurethane resin and the hollow particles is good, but when using non-expandable hollow particles, the particle diameter of the hollow particles does not change when heated, so the force of pushing against the polyurethane resin is weaker than that of expandable hollow particles. Also, when the particle diameter of the hollow particles is small, the thickness of the shell is thick to maintain the hollow structure. Here, in the case of expandable hollow particles, the thickness of the shell becomes thin due to expansion by heating, but in the case of non-expandable hollow particles, the particle diameter does not change even when heated, so the thickness of the shell is thick. For this reason, when the particle diameter of the hollow particles is small, the non-expandable hollow particles contained in the polishing layer are harder than the expanded hollow particles contained in the polishing layer. For this reason, when a block containing urethane resin and hollow particles is sliced to form an abrasive layer, the hollow particles are not properly cut by the blade used for slicing, resulting in peeling and deformation of the hollow particles. This makes it easy for scratches to occur when polishing an object to be polished. In contrast, according to this embodiment, the hollow particles 11C are modified on the surface of the outer shell 11C1 and have reactive functional groups that react with at least one of the isocyanate group-terminated urethane prepolymer and the curing agent, and therefore are non-expanding and have a particle size (D 50 Even when small hollow particles 11C having a diameter of 1 μm or more and 20 μm or less are used, the adhesion between urethane resin 11B and hollow particles 11C can be improved. This makes it possible to suppress peeling or deformation of hollow particles 11C when slicing a block containing urethane resin 11B and hollow particles 11C, thereby reducing the occurrence of scratches.
[0052] <<<Polishing equipment>>> The polishing pad is incorporated in a polishing apparatus for use. The polishing apparatus 20 shown in FIG. 3 is a chemical mechanical polishing apparatus. The polishing apparatus 20 includes a polishing pad 10, a polishing platen 21 to which the polishing pad 10 is attached by a double-sided tape (not shown) or the like provided on the cushion layer 12 of the polishing pad 10, a holding platen 22 for holding the object to be polished 30, and a slurry supplying unit 23 for supplying a slurry when polishing the object to be polished 30. The polishing pad 10 rotates together with the polishing platen 21 with the object to be polished 30 pressed against the surface 10A of the polishing pad 10, and polishes the object to be polished 30. At that time, a slurry is supplied from the slurry supplying unit 23 between the polishing pad 10 and the object to be polished. The slurry is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the polishing effect is increased by the relative movement with the object to be polished 30 while the chemical components and abrasive grains in the slurry are flowing. The slurry is supplied to and discharged from the polishing surface through grooves or holes (not shown) provided in the polishing layer 11 . EXAMPLES
[0053] In order to explain the present invention in detail, the following examples are given, but the present invention is not limited to these. Figures 4 to 7 are SEM images of the surfaces of the polishing layers of the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2 at magnifications of 1000 and 5000.
[0054] <Example 1> First, an isocyanate-terminated urethane prepolymer (1), an isocyanate-terminated urethane prepolymer (2), a curing agent, and non-expanding hollow particles (1) (product number "Techpolymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.) were prepared. The isocyanate-terminated urethane prepolymer (1) was obtained by reacting 2,4-tolylene diisocyanate (2,4-TDI), polypropylene glycol (PPG1000) having a number average molecular weight of 1000, and diethylene glycol (DEG), and had an NCO equivalent of 560. The isocyanate-terminated urethane prepolymer (2) was obtained by reacting 2,4-tolylene diisocyanate (2,4-TDI), butylene glycol adipate ester having a number average molecular weight of 2000, and diethylene glycol (DEG), and had an NCO equivalent of 600. The weight ratio of the isocyanate-terminated urethane prepolymer (1) and the isocyanate-terminated urethane prepolymer (2) was 1:1. As the curing agent, 4,4-methylenebis(2-chloroaniline) (MOCA) was prepared. The hollow particles (1), Techpolymer (registered trademark), have hydroxyl groups modified on the surface and have a particle size (D 50 ) was 4 to 6 μm.
[0055] Next, the isocyanate group-terminated urethane prepolymer and hollow particles were mixed, heated to 65°C, and degassed under reduced pressure. The curing agent MOCA was dissolved at 120°C and degassed under reduced pressure. Then, the isocyanate group-terminated urethane prepolymer, the curing agent, and the hollow particles were mixed so that the content of hollow particles was 5% by mass relative to 100 parts by mass of the isocyanate group-terminated urethane prepolymer. The resulting mixture was poured into a mold and cured primarily at 80°C for 30 minutes. The formed block body containing the urethane resin and hollow particles was removed from the mold and cured secondary at 120°C for 4 hours in an oven. The resulting block body was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours. The resulting block body was sliced in a direction perpendicular to the thickness direction of the block body to create a polishing layer with a thickness of 1.3 mm, and a double-sided tape was attached to the back side of this polishing layer to form a polishing pad.
[0056] <Example 2> In Example 2, a polishing pad was obtained in the same manner as in Example 1, except that the content of the hollow particles was 10% by mass.
[0057] <Comparative Example 1> In Comparative Example 1, a polishing pad was obtained in the same manner as in Example 1, except that non-expandable hollow particles (2) (product number "Tech Polymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.) were used instead of the hollow particles (1) (product number "Tech Polymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.). The Tech Polymer (registered trademark) which is the hollow particle (2) has a carboxyl group modified on the surface, and the particle size (D 50 ) was 4 to 6 μm.
[0058] <Comparative Example 2> In Comparative Example 2, a polishing pad was obtained in the same manner as in Example 1, except that expandable hollow particles (3) (product number "Expancel (registered trademark) 461DU20", manufactured by Nippon Fillite Co., Ltd.) were used instead of the hollow particles (1) (product number "Tech Polymer (registered trademark)", manufactured by Sekisui Chemical Co., Ltd.). The "Expancel (registered trademark) 461DU20" which is the hollow particle (3) is not modified with a functional group on the surface, and the particle size (D 50 ) in the unexpanded state was 6 to 8 μm.
[0059] The formulations of the curable compositions for the polishing layer used in Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Table 1.
Table 1
[0060] <SEM Image Observation> In the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2, the surface of the polishing layer was observed at magnifications of 1000 times and 5000 times using a scanning electron microscope (SEM, product name "JSM-5000LV", manufactured by JEOL Ltd.).
[0061] <Arithmetic mean height (Sa) measurement> The arithmetic mean height (Sa) of the surface of the polishing layer of the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2 was measured. Specifically, the measurement was performed under the following measurement conditions using a laser microscope VK-X1000 (model name) manufactured by KEYENCE Corporation. (Measurement conditions) Lens: X20 ·Measurement area: 600μm×700μm Measurement mode: Laser confocal Analysis software: KEYENCE multi-file analysis application
[0062] <Measurement of density of polishing layer> The density of the polishing layer was measured for the polishing layers of the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, the measurement was performed in accordance with the Japanese Industrial Standard (JIS K 6505:1995).
[0063] <Shore D hardness measurement of polishing layer> The Shore D hardness was measured for the polishing layers of the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2. Specifically, the Shore D hardness was measured using a D-type hardness tester in accordance with the Japanese Industrial Standards (JIS K 6253-1 and 6253-3:2012). Here, the measurement sample was obtained by stacking multiple polishing layers as necessary so that the total thickness was at least 4.5 mm or more.
[0064] <Measurement of average pore diameter> The pore diameter of the polishing layer of the polishing pad according to Examples 1 and 2 and Comparative Examples 1 and 2 was measured to obtain the average pore diameter. Specifically, three areas (each a rectangle of 0.5 mm long x 0.7 mm wide) were selected from the surface of the polishing layer without bias, and each area was observed at 400 times magnification using a laser microscope (product name "VK-X1000", manufactured by KEYENCE Corporation). Each image obtained (rectangle of 0.5 mm long x 0.7 mm wide) was binarized using image processing software (software name "WinROOF2018 Ver4.0.2", manufactured by Mitani Shoji Co., Ltd.) to confirm the pores, and the circle equivalent diameter (pore diameter) was calculated from the area of each pore. The cutoff value (lower limit) of the pore diameter was set to 1 μm, and noise components were excluded. Then, all the pore diameters contained in each of the above areas (images) were averaged to calculate the average pore diameter of each area. The average pore diameters of the three regions thus obtained were then averaged to calculate the final average pore diameter.
[0065] <Polishing test> Using the polishing pads of Examples 1 and 2 and Comparative Examples 1 and 2, polishing tests were carried out under the following polishing conditions.
[0066] (polishing conditions) Polishing machine used: F-REX300X (manufactured by Ebara Corporation) Disk:34J (KINIK) Abrasive temperature: 20℃ Polishing platen rotation speed: 85 rpm Polishing head rotation speed: 86 rpm Grinding pressure: 1.18psi Polishing slurry (metal film): CSL-9044C (CSL-9044C stock solution: pure water = mixed solution of 1:9 by weight) (manufactured by Fujimi Corporation) Polishing slurry flow rate: 200ml / min Polishing time: 60 seconds Polished object (metal film): Cu film substrate (disc-shaped, 300 mm in diameter) Pad break: 32N, 10 minutes Conditioning: Ex-situ, 32N, 4 scans
[0067] (Scratch evaluation) Using the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2, four Cu film substrates were polished under the above-mentioned polishing conditions, and defects (surface defects) with a size of 110 nm or more were detected on the entire Cu film substrate after polishing using a high sensitivity measurement mode of a wafer surface inspection device (product name "Surfscan SP5", manufactured by KLA Tencor Corporation). For each detected defect, an SEM image taken using a review SEM was analyzed, and the defects were classified into "particles," "pad debris," and "scratches," and the number of scratches among them was counted. The results were the average value of the results obtained by polishing four Cu film substrates. The classification "particles" refers to fine particles remaining on the surface of the substrate, the classification "pad debris" refers to debris of the polishing layer attached to the surface of the substrate, and the classification "scratches" refers to scratches on the surface of the substrate.
[0068] (polishing rate) Using the polishing pads according to Examples 1 and 2 and Comparative Examples 1 and 2, the polishing rate (Å / min) of the polished substrate was measured under the above-mentioned polishing conditions as follows. First, the Cu film substrate before and after the polishing test was measured in the diameter direction on the Cu film substrate, and the thickness at those points before and after the polishing test was measured. Then, based on the measured thickness, the average thickness before the polishing test and the average thickness after the polishing test were calculated, and the average polished thickness was calculated by calculating the difference between these average values. Then, the polishing rate was calculated by dividing the obtained average polished thickness by the polishing time. The thickness was measured using a four-probe sheet resistance measuring device (product name "RS-200", manufactured by KLA Tencor Corporation, measurement: DBS mode).
[0069] The results are shown in FIGS. [Table 2]
[0070] As shown in Table 2, the polishing pads according to Examples 1 and 2 had fewer scratches and a higher polishing rate than Comparative Example 2. It can be seen from Table 2 that the polishing pad according to Comparative Example 1 could not be accurately measured because the hollow particles fell off from the polishing layer. Also, as shown in FIG. 6, peeling and deformation of the hollow particles were observed on the surface of the polishing layer of the polishing pad according to Comparative Example 1. In contrast, peeling and deformation of the hollow particles were not observed on the surface of the polishing layer of the polishing pads according to Examples 1 and 2, as shown in FIGS. 4 and 5. Therefore, it was confirmed that the occurrence of scratches can be reduced by modifying the surface of the hollow particles with hydroxyl groups. [Explanation of symbols]
[0071] 10...Polishing pad 11...polishing layer 11A…Surface 11B…Polyurethane resin 11C...Hollow particle 11C1…Outer shell 12…Cushion layer 20...polishing device
Claims
1. A polishing pad having a polishing layer containing a polyurethane resin and hollow particles dispersed in the polyurethane resin, the polishing layer is a cured product of a curable resin composition containing an isocyanate group-terminated urethane prepolymer, a curing agent, and non-expanding hollow particles; The particle diameter of the hollow particles (D 50 ) is 1 μm or more and 20 μm or less, The polishing pad comprises hollow particles each having an outer shell and a reactive functional group modified on the surface of the outer shell and capable of reacting with at least one of the isocyanate group-terminated urethane prepolymer and a curing agent.
2. 2. The polishing pad according to claim 1, wherein the reactive functional group is a functional group that reacts with the isocyanate-terminated urethane prepolymer.
3. The polishing pad of claim 1 , wherein the reactive functional group is a hydroxyl group.
4. 2. The polishing pad according to claim 1, wherein the polishing layer has a surface having pores, the pores having an average opening diameter of 1 μm or more and 20 μm or less.
5. A polishing apparatus comprising the polishing pad according to claim 1 .
6. A method for producing a polishing pad having a polishing layer containing a polyurethane resin and hollow particles dispersed in the polyurethane resin, comprising: A step of curing a curable resin composition containing an isocyanate group-terminated urethane prepolymer, a curing agent, and non-expandable hollow particles to obtain a block containing a urethane resin and hollow particles; and a step of slicing the block to form an abrasive layer. The particle diameter of the hollow particles (D 50 ) is 1 μm or more and 20 μm or less, The method for producing a polishing pad comprises the steps of: providing a hollow particle having an outer shell; and modifying a surface of the outer shell with a reactive functional group that reacts with at least one of the isocyanate group-terminated urethane prepolymer and a curing agent.
7. The method for producing a polishing pad according to claim 6 , wherein the reactive functional group is a functional group that reacts with the isocyanate group-terminated urethane prepolymer.
8. The method for producing a polishing pad according to claim 6 , wherein the reactive functional group is a hydroxyl group.
9. The method for producing a polishing pad according to claim 6 , wherein the polishing layer has a surface having pores, the pores having an average opening diameter of 1 μm or more and 20 μm or less.
Citation Information
Patent Citations
Composition, chemical mechanical polishing pad, and chemical mechanical polishing method
JP2012182314A